Advances in the use of nanomicelles to enhance the efficacy of antitumour substances (review) - E. V. Sanarova; L. L. Nikolaeva; S. D. Shceglov; Zh. M. Kozlova; O. L. Orlova; N. A. Oborotova; A. V. Lantsova (Разработка и регистрация лекарственных средств)
Introduction. The influence of the dosage form on the pharmacological effect has been known since ancient times. The strategy for the preparation of micellar dosage forms for active antitumour substances was formulated in the last century. However, it has become widespread in practice in recent decades. This is largely due to advances in the synthesis of new structural components for the formation of micellar carrier, as well as to the acquisition of better knowledge of biochemical processes occurring in the tumour cell.Text. This review is devoted to the achievements in the field of application of nanomicellar forms of antitumor drugs to improve the effectiveness of cancer therapy, which cover the period from 2019 to 2024. For this purpose, excipients used to obtain nanomicellar forms of antitumor substances are considered and analyzed, using docetaxel, paclitaxel, doxorubicin, and photosensitizers as examples. The creation of micellar forms allowed us to take a new look at these substances known in oncological practice.Conclusion. Available achievements in the field of nanomicelles application for increasing the effectiveness of antitumour substances undoubtedly show the promising development of this technological direction. However, there are still many unresolved issues related to the stability of nanomicelles when administered into the body, as well as legal regulation in the field of creation and introduction of this new pharmaceutical form. These questions still need to be resolved by pharmaceutical science.